Bridging the Care Gap: Enhancing Self-Efficacy and Practice in Early Postnatal Care through Midwifery Initiatives - Tamilthendral Ravikumar; Sumathi Chandran; Shankar Shanmugam Rajendran; Vanitha Narayanasamy Naidu; Kalvikkarasi narayanasamy; Meenakshi Prabhakar; Sharmila Samson jayaprakash (The Bioscan, 2025)
Postpartum minor ailments are common yet often neglected concerns that can adversely affect new mothers' recovery and psychological well-being. Inadequate self-efficacy and lack of awareness about self-care contribute to poor health outcomes during the early postnatal period. Midwives, through structured education and support, can empower primi para mothers to manage postpartum discomforts effectively. This study examines the impact of a midwife-driven initiative on self-efficacy and self-reported practices among postnatal mothers in a tertiary care setting. A quasi-experimental, non-randomised control group design was employed. Sixty primipara mothers were selected through purposive sampling and divided equally into experimental and control groups. The experimental group received structured midwife-driven educational sessions over four weeks, focusing on perineal care, rest, backache, breast care, fatigue, and other postpartum discomforts. Standard postnatal care was given to the control group. Statistical analyses included descriptive statistics, Chi-square tests, and McNemar’s test.The midwife-driven initiative markedly enhanced mothers’ self-efficacy and self-reported practices regarding postpartum minor ailments. Incorporating such interventions into routine postnatal care may significantly improve maternal health and recovery.